Arabidopsis thaliana ubiquitin-associated protein 2 (AtUAP2) functions as an E4 ubiquitin factor and negatively modulates dehydration stress response - Cho-Rong Park; Ji-Hee Min; Ying Gong; Hyunkyu Sang; Kyeong-Hwan Lee; Cheol Soo Kim (Plant Molecular Biology, 2024)

Increased Cysteine Accumulation is Essential for Salt Stress Tolerance in Arabidopsis Halotolerance 2-Like (AHL)-Overexpressing Transgenic Plants - Tinh Van Nguyen; Jeong-In Kim; Cho-Rong Park; Moon-Soo Chung; Cheol Soo Kim (Journal of Plant Biology, 2021)

CU06-1004 (endothelial dysfunction blocker) ameliorates astrocyte end-feet swelling by stabilizing endothelial cell junctions in cerebral ischemia/reperfusion injury - Dong Young Kim; Haiying Zhang; Songyi Park; Yeaji Kim; Cho-Rong Bae; Young-Myeong Kim; Young-Guen Kwon (Journal of Molecular Medicine, 2020)
Cerebral ischemia, or stroke, is widespread leading cause of death and disability. Surgical and pharmacological interventions that recover blood flow are the most effective treatment strategies for stroke patients. However, restoring the blood supply is accompanied by severe reperfusion injury, with edema and astrocyte end-feet disruption. Here, we report that the oral administration of CU06-1004 (previously Sac-1004), immediately after onset of ischemia/reperfusion (I/R), ameliorated cerebral damage. CU06-1004 stabilized blood‑brain barrier by inhibiting the disruption of the tight junction-related protein zona occludens-1 and the cortical actin ring in endothelial cells (ECs) after I/R. Interestingly, CU06-1004 significantly suppressed astrocyte end-feet swelling following I/R, by reducing aquaporin 4 and connexin 43 levels, which mediates swelling. Furthermore, the degradation of β1-integrin and β-dystroglycan, which anchors to the cortical actin ring in ECs, was inhibited by CU06-1004 administration after I/R. Consistently, CU06-1004 administration following I/R also suppressed the loss of laminin and collagen type IV, which bind to the cortical actin ring anchoring proteins. Unlike the protective effects of CU06-1004 in ECs, astrocyte viability and proliferation were not directly affected. Taken together, our observations suggest that CU06-1004 inhibits I/R-induced cerebral edema and astrocyte end-feet swelling by maintaining EC junction stability. Key messages • CU06-1004 ameliorates I/R-induced cerebral injury. • EC junction integrity was stabilized by CU06-1004 treatment after I/R. • CU06-1004 reduces astrocyte end-feet swelling following I/R. • EC junction stability affects astrocyte end-feet structure maintenance after I/R.

Sulfuretin induces osteoblast differentiation through activation of TGF-β signaling - No-Joon Song; So-Mi Kwon; Suji Kim; Hyang-Jin Yoon; Cho-Rong Seo; Byunghyun Jang; Seo-Hyuk Chang; Jin-Mo Ku; Jeong-Soo Lee; Ki-Moon Park; Joung-Woo Hong; Geun Hyung Kim; et al. (Molecular and Cellular Biochemistry, 2015)

Soluble overexpression and purification of bioactive human CCL2 in E. coli by maltose-binding protein - Thu Trang Thi Vu; Bon-Kyung Koo; Jung-A Song; Seon-Ha Chong; Cho Rong Park; Minh Tan Nguyen; Boram Jeong; Han-Bong Ryu; Jae Young Seong; Yeon Jin Jang; Robert Charles Robinson; Han Choe (Molecular Biology Reports, 2015)

Peroxisome-localized hepatitis Bx protein increases the invasion property of hepatocellular carcinoma cells - Jae-Min Han; Jung-Ah Kang; Min-Hee Han; Kyung-Hun Chung; Cho-Rong Lee; Woo-Keun Song; Youngsoo Jun; Sung-Gyoo Park (Archives of Virology, 2014)